In Situ Observation of Solar-flare-induced Proton Cyclotron Waves Upstream from Mars - Lin, Haibo; Guo, Jianpeng; Masunaga, Kei; Seki, Kanako; Mazelle, Christian; Zhao, Dan; Huang, Hui; Zhao, Juan; Wei, Yong; Liu, Libo (The Astrophysical journal, 2022)
Proton cyclotron waves (PCWs) upstream from Mars are usually interpreted as waves generated by ion/ion instabilities due to the interaction between the solar wind plasma and the pickup protons, originating from the extended hydrogen (H) exosphere of Mars. Their generation mainly depends on the solar wind properties and the relative density of the newborn protons with respect to the background solar wind. Under stable solar wind conditions, a higher solar irradiance leads to both increased exospheric H density and ionization rate of H atoms, and therefore a higher relative density, which tends to increase the linear wave growth rate. Here we show that the solar irradiance is likely to contribute significantly to PCW generation. Specifically, we present observations from the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft indicating that, around the peak of the X8.2 flare on 2017 September 10, the increased solar irradiance gave rise to higher pickup H + fluxes, which in turn excited PCWs. This result has implications for inferring the loss of hydrogen to space in early Martian history with more intense and frequent X-class flares as well as their contributions to the total loss.